Kinerja Kebijakan One Village One Product (OVOP) dalam Peningkatan Potensi Ekonomi di Kabupaten Brebes - Aswhar Anis (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
The purpose of this study is to investigate and analyze the performance as a form of policy successes One Village One Product (OVOP) in Brebes Regency. This research uses descriptive qualitative research with the aim of providing a picture or describe the state of the object. The study was conducted in the Brebes Regency, covering areas that were targeted OVOP program, and the Department of Industry and Trade Office Department of Cooperatives and UKM As well as the center of the main data source. Descriptive qualitative data analysis, which illustrate the descriptions based on the data available on the object of research. The results show the achievement of performance OVOP policy in improving the welfare of the community in Brebes Regency has not reached optimal results, from some of the leading products available in the Brebes Regency, two new products, the main target is the implementation of OVOP programs salted egg and seaweed, while the center other products are still in development stage. However, of the activities that have been done show a considerable increase prospectively, including an increase in the volume of production and the birth of new product variants as a result of the coaching and development of creativity and innovation entrepreneurs. As a supporter of factors, including Brebes Regency Government has a strong commitment to implement the OVOP program on an ongoing basis, so as to exploit the full potential that can be used as a superior product. Availability of funds, human resources and compliance infrastructure needs, especially for the target group can be used as capital to implement the OVOP activities thoroughly. The stages of activities have been implemented in an integrated manner and in accordance with their respective authorities, although there are indications of overlapping authorities in carrying out coaching because there are no clear boundaries in determining the category of individual businesses, and industry groups.